DEMOGRAPHIC, CLINICO-PATHOLOGICAL PROFILE, AND IMMUNOHISTOCHEMISTRY STUDY IN FEMALE BREAST CANCER IN EASTERN INDIA: A HOSPITAL-BASED RETROSPECTIVE STUDY - DAS, PABITRA; DAS, SUNITA; JANA, ARPAN; KUMAR DAS, TAPAS (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Female breast cancer is the most common cancer in Worldwide. In India, locally advanced female breast cancer is more common (57%) and survival rate of female breast cancer is very poor because early age of disease onset, diagnosed in late stage, delayed initiation, and inadequate proper treatment. Few studies have been published in journals regarding clinico-pathological profile of breast cancer in India. However, there are limited data available in literature on demographic, clinico-pathological profile, and immunohistochemistry (IHC) study in female breast cancer in Eastern India. Methods: Newly diagnosed, histopathology proved female breast cancer patients registered from January 2018 to June 2022 at department of radiotherapy was included in this study. This study was retrospective and primary data were collected from medical records of patients about their demographic, clinico-pathological, and IHC profile. Results: The median age at diagnosis was 48 years. Incidence of female breast cancer was more in the age group of 41–50 years (39.5%) and most of the patients were in premenopausal group (59.2%). Locally advance disease, Stage III (50.7%) was more followed by Stage II (32.2%). Most common histopathology type was invasive ductal carcinoma not otherwise specified (90.8%) and Grade II (50%). Triple negative breast tumor was more common IHC type (32.9%). Conclusions: In our study, locally advanced breast cancer was more common in premenopausal patients in urban area. Awareness regarding breast cancer among general population, early diagnosis and adequate proper treatment can reduce mortality of breast cancer.